PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI MENGURUTKAN DAN MEMBANDINGKAN DATA PADA SISWA KELAS III UPT SDN SENDANGHARJO IV - Shobihatul Mubarokah; Sumadi; Sri Wahyuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This Classroom Action Research aimed to improve students' mathematics learning outcomes on the topic of sorting and comparing data through the implementation of the Problem Based Learning (PBL) model for third-grade students at UPT SDN Sendangharjo IV. The study employed the Kemmis and McTaggart Classroom Action Research model, which consists of four stages: planning, action, observation, and reflection, conducted in two cycles. The research subjects were 21 third-grade students. Data were collected through observation, achievement tests, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of the Problem Based Learning model significantly improved students' mathematics learning outcomes. The average score increased from 50.0 in the pre-cycle to 71.9 in Cycle I and 88.8 in Cycle II. The percentage of students achieving mastery learning also improved from 23.8% in the pre-cycle to 61.9% in Cycle I and finally reached 90.4% in Cycle II. In addition, students' learning activities increased through group discussions, problem-solving activities, and group presentations. Therefore, the Problem Based Learning model is effective in improving mathematics learning outcomes on the topic of sorting and comparing data for elementary school students.